2012
DOI: 10.1007/s10900-012-9540-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effectiveness of a Community-Based Sensitization Strategy in Creating Awareness About HPV, Cervical Cancer and HPV Vaccine Among Parents in North West Cameroon

Abstract: In 2010, the Cameroon Baptist Convention Health Services (CBCHS) received a donation of HPV vaccine (Gardasil®) to immunize girls of ages 9-13 years in the North West Region of Cameroon. We evaluated the effectiveness of the CBCHS campaign program in sensitizing parents/guardians to encourage HPV vaccine uptake, identified factors that influence parents' decisions to vaccinate girls, and examined the uptake of cervical cancer screening among mothers. We conducted a cross-sectional survey in four healthcare fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
48
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 43 publications
6
48
1
1
Order By: Relevance
“…This affirms the WHO assertion many years ago that in most developing countries, only 5% of the women at any point in time had been screened for cervical cancer [29,30]. The figure is also in tune (though lower) with the screening coverage levels in Nigeria and most of sub-Saharan Africa which is generally below 10% [22]. The screening coverage ranges from 5.2% in Ibadan, 4.7% in Ago-Iwoye,8.7% in Sagamu,and 4.4% in Sokoto [31][32][33][34].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This affirms the WHO assertion many years ago that in most developing countries, only 5% of the women at any point in time had been screened for cervical cancer [29,30]. The figure is also in tune (though lower) with the screening coverage levels in Nigeria and most of sub-Saharan Africa which is generally below 10% [22]. The screening coverage ranges from 5.2% in Ibadan, 4.7% in Ago-Iwoye,8.7% in Sagamu,and 4.4% in Sokoto [31][32][33][34].…”
Section: Discussionsupporting
confidence: 80%
“…In Enugu, the awareness significantly varied with the level of educational attainment [21]. High level of awareness about cervical cancer was also found in North-west Cameroon [22]. Higher levels of awareness were found among students and healthcare workers.…”
Section: Discussionmentioning
confidence: 92%
“…This is consistent with studies that have established high HPV vaccine uptake among comparable adolescent populations [12], [21], [22], [34]. The relatively high parental acceptability of hypothetically vaccinating their sons with HPV vaccines is also consistent with commentaries from elsewhere [10], [19], [37].…”
Section: Discussionsupporting
confidence: 88%
“…Most participants in our study heard about cervical cancer before their interview explaining why knowledge level about cervical cancer and cervical cancer screening was higher in our study compared to the other study conducted in Burkina [12] which found a lower proportion of participants who previously heard about cervical cancer. Awareness about cervical cancer, HPV and HPV vaccination in North West Cameroon also found level of education to be an influencing factor in a parents understanding of the disease and decision to allow their daughters to be vaccinated [31]. In Lagos, Nigeria, education was also related to a woman being willing to have screening for cervical cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…Income level and cost of screening, which is related to a patient’s or a patient’s family’s employment, was found to be an important factor in other studies investigating cervical cancer screening barriers. These studies in Northwest Cameroon [31], Southeast Nigeria [19], and Botswana [18] found higher income or reduced costs of screening to be related to better screening rates. Additionally, an assessment of cervical cancer screening in low-income countries found household SES and a country’s health expenditure to be determinants of cervical and breast cancer screening rates [33].…”
Section: Discussionmentioning
confidence: 99%